Rekomendasi Tata Kelola IT dengan Acuan Cobit 5 pada Struktur Organisasi Sekolah Vokasi - Dwiyono Ariyadi; Indah Puji Astuti (Jurnal Manajemen Informatika (JAMIKA), 2021)
Vocational education institutions will be able to carry out their functions and objectives if they have supporting elements that contribute to the goals of the institution. One of the supporting elements is resources. Various resources in vocational institutions have a role to accelerate the realization of institutional goals. Information technology resources play a role in facilitating the activities of institutions in the IT field. The purpose of this study is to know whether the organizational structure that handles IT in schools SMK Jenangan is an appropriate IT governance COBIT. The methodology used by the descriptive. survey research data. Based on the findings obtained, this institution is still lacking staff in different positions. After conducting research obtained, there are 5 primary IT-related goals of 20 processes COBIT5. The result is an adjustment in the form of recommendation IT governance resources requirements along with the tasks and responsibilities which refers COBIT5 domain. The hope of research is the impact to changes in the organizational structure typewriter appropriate recommendations so software engineering division can optimal tasks.